Morphology, mineralogy and engineering characteristics of Tanjung Bin bottom ash [electronic resource] - 434934 Lee, Food Wei; Fakulti Kejuruteraan Awam (2008)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2008